THEORETICAL BASIS OF THE FORMATION AND DEVELOPMENT OF THE FOOD MARKET - Abdurahmonov Adxamjon Sultonboyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article presents a grouping of studies revealing the essence of the food market and summarizes modern approaches. An improved author’s definition of the food market has been developed. Segmentation was carried out and hierarchical levels were determined based on the functions of the food market. Scientific conclusions and practical recommendations on the implementation of complex measures in the food market have been developed.